A SuperQuat glycolate aldol approach to the asymmetric synthesis of hexose monosaccharides. - Davies, S; Nicholson, R; Smith, A (2005)
A stereoselective two-carbon homologation protocol has been developed and applied to the asymmetric synthesis of the hexose monosaccharides D-galactose, D-fucose, D-idose, D-6-deoxyidose, D-talose and D-6-deoxytalose.